PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA (2019–2022) - Silalahi, Donalson; Sitanggang, Evi Junita; Silalahi, Esli (Jurnal Manajemen dan Bisnis, 2025)
This study aims to determine and analyze the effect of managerial ownership, institutional ownership, and independent boards of commissioners on stock prices in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study was 26 food and beverage manufacturing companies. The sampling technique used was purposive sampling, resulting in 10 food and beverage manufacturing companies. Data analysis techniques used were multiple linear regression and descriptive statistical analysis. Hypothesis testing used t-tests and F-tests at a 5 percent significance level. The results showed that partially, managerial ownership had a negative and significant effect on stock prices, institutional ownership had a negative and significant effect on stock prices, and independent boards of commissioners had a positive and insignificant effect on company stock prices. Simultaneously, managerial ownership, institutional ownership, and independent boards of commissioners explained 43.7 percent of stock price variation.